Pleuroperitoneal true diaphragmatic hernia of the liver in a cat - Pilli, Mehmet; Özgencil, Fatma E.; Seyrek-Intas, Deniz; Gültekin, Cagri; Turgut, Kürsad (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2020)
A 2-year old female domestic shorthair cat was referred with intermittent vomiting. Laboratory analyses revealed only an elevated alanine aminotransferase activity. Plain thoracic radiographs showed a right-sided transdiaphragm protrusion of a liver lobe into the thoracic cavity. On abdominal ultrasound the diaphragm and liver parenchyma also presented a bulge towards the thoracic cavity. By cranial median laparotomy herniation of the quadrate liver lobe through the right aspect of the diaphragm into the thoracic cavity was confirmed. The protruding quadrate liver lobe was covered by intact parietal peritoneum. Following relocation of the liver lobe the defect was closed. Postoperatively the intermittent vomiting stopped. The purpose of this case report was to present plain radiography and abdominal ultrasonography as effective tools in the diagnosis of this rare and usually asymptomatic true herniation case along with its operative treatment.
Keywords: Cat; true diaphragmatic hernia; pleuroperitoneal hernia; ALT